2018
DOI: 10.18203/2320-1770.ijrcog20184929
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between obstetric outcome and amniotic fluid index (AFI) in preterm prelabour rupture of membranes (PPROM)

Abstract: Background: The purpose was to determine whether AFI<5 cm after preterm premature rupture of the membranes (PPROM) is associated with an increased risk of maternal and perinatal morbidity.Methods: We performed a prospective case control study of 161 singleton pregnancies complicated by preterm prelabour rupture of the membranes (PPROM) in whom AFI was assessed. Patients were categorized in two groups on the basis of amniotic fluid index- AFI<5 cm or AFI ≥ 5 cm. Categorical data were tested for significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Indeed, comparable to findings in our cohort, lack of association between AFI scores and adverse outcomes in pregnancies complicated by PPROM was also reported in other studies [5,15]. In a past study of 161 singleton pregnancies complicated by PPROM, authors reported that AFI < 5 cm and AFI ≥ 5 cm were similar in terms of gestational age at rupture of the membranes, gestational age at the delivery, mode of delivery, maternal chorioamnionitis, abruption, early onset neonatal sepsis and NICU stay as well as fetal birth weight [5]. No significant association of AFI with APGAR scores, neonatal RDS and maternal chorioamnionitis was also reported in another study [15].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Indeed, comparable to findings in our cohort, lack of association between AFI scores and adverse outcomes in pregnancies complicated by PPROM was also reported in other studies [5,15]. In a past study of 161 singleton pregnancies complicated by PPROM, authors reported that AFI < 5 cm and AFI ≥ 5 cm were similar in terms of gestational age at rupture of the membranes, gestational age at the delivery, mode of delivery, maternal chorioamnionitis, abruption, early onset neonatal sepsis and NICU stay as well as fetal birth weight [5]. No significant association of AFI with APGAR scores, neonatal RDS and maternal chorioamnionitis was also reported in another study [15].…”
Section: Discussionsupporting
confidence: 93%
“…Early recognition and appropriate treatment of PPROM is crucial for preventing potential adverse perinatal outcomes related to prematurity (i.e. neonatal morbidity and mortality) and for minimizing the risk of fetal and maternal complications [3][4][5][6]. However, PPROM continues to be a challenging condition in current obstetric practice in terms of controversies regarding the optimal timing and route of delivery to minimize maternal and perinatal morbidity [3,5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations